Sustainable valorization of co-products from asparagus cultivation by obtaining bioactive compounds - Alcaide, Isabel Viera; Hamdi, Amel; Guilleín-Bejarano, Rafael; Jiménez-Araujo, Ana; Rodríguez-Arcos, Rocío (Frontiers in Plant Science, 2023)
Asparagus cultivation generates every year a significant amount of by-products that consist of root and frond. Leaving these residues on the fields after harvesting negatively affects the following asparagus crops, since they release autotoxic substances, whose accumulation causes that asparagus yields gradually decrease over the years, becoming an unprofitable crop in a period of about 10 to 15 years. This phenomenon is known as decay. On the other hand, once a certain plantation has been lifted, it is not profitable to immediately re-plant new asparagus plants, being necessary to wait an average of 4 or 5 years. This phenomenon is known as the replanting problem, and causes the need to continually search for new land. Another added problem is that the elimination of residues from asparagus cultivation entails significant economic costs. For all these reasons, it is essential to seek alternatives that improve the sustainability of the crop within the scope of the circular economy. This work proposes the valorization of asparagus by-products by obtaining bioactive compounds. Main objectives include: i) phytochemical analyses of asparagus fronds and roots; ii) obtaining bioactive extracts, with distinct technological and nutritional functionalities, by using an environmentally sustainable extraction process, easy to implement in the practice of a food industry and with methods compatible with food use. Characterization of asparagus by-products shown that fronds had an average flavonoid content of 2.637 ± 0.014 g/Kg fresh weight, which is up to 5-6 times higher than that of the spears; and roots contained up to 10 times more saponins (2.25 g/Kg fresh weight), which were accompanied by lower quantities of phenolic acids (368 mg/Kg fresh weight). Statistical analysis revealed that those phytochemical contents were mainly determined by location and phase of the vegetative cycle. The proposal for the recovery and valorization of asparagus by-products is based on obtaining two bioactive extracts, the first being an antioxidant extract enriched in flavonoids, with an average yield of 10.7 g/Kg fresh frond and the second, a saponins extract with an average yield of 10.3 g/Kg fresh root. These extracts have great techno-functional potential in the agri-food industry.